Equivalent Circuit Analysis of the Disk-Loaded Coaxial Structure for MILO - Dixit G.; Jain P.K. (My University, 2025)
An axially periodic metal disk-loaded coaxial cylindrical waveguide structure has been analyzed using the equivalent circuit approach. In the structure model, all the space harmonics generated due to the structure axial periodicity in the disk-free region and modal harmonics caused due to reflections from the metal disks have been considered. The actual structure has been replaced by an equivalent transmission line in terms of its circuit parameters. Considering a loss-free situation, only two parameters, the series inductance and shunt capacitance per unit length of the line, remain and have been derived independently. Here, only a half set of the structure EM field expressions and boundary conditions has been required in the analysis at a time, which has made the analysis simpler. The dispersion results obtained here exactly passed on to those obtained through the field analysis. It has also been found that the structure dispersion can be controlled by varying the disk hole and periodicity of the structure. The analysis has been carried here for the slow wave, TM 0n operating mode; however, the approach is general and could easily be extended to the fast wave or TE mn mode as well. © 1973-2012 IEEE.